The crystal structure of shikimate dehydrogenase (AroE) reveals a unique NADPH binding mode. - Ye, S; von Delft, F; Brooun, A; Knuth, M; Swanson, R; McRee, D (2003)
Shikimate dehydrogenase catalyzes the NADPH-dependent reversible reduction of 3-dehydroshikimate to shikimate. We report the first X-ray structure of shikimate dehydrogenase from Haemophilus influenzae to 2.4-A resolution and its complex with NADPH to 1.95-A resolution. The molecule contains two domains, a catalytic domain with a novel open twisted alpha/beta motif and an NADPH binding domain with a typical Rossmann fold. The enzyme contains a unique glycine-rich P-loop with a conserved sequence motif, GAGGXX, that results in NADPH adopting a nonstandard binding mode with the nicotinamide and ribose moieties disordered in the binary complex. A deep pocket with a narrow entrance between the two domains, containing strictly conserved residues primarily contributed by the catalytic domain, is identified as a potential 3-dehydroshikimate binding pocket. The flexibility of the nicotinamide mononucleotide portion of NADPH may be necessary for the substrate 3-dehydroshikimate to enter the pocket and for the release of the product shikimate.